Intense community dynamics in the pre-Roman frontier site of Fermo (ninth–fifth century BCE, Marche, central Italy) inferred from isotopic data - Carmen Esposito; Melania Gigante; Federico Lugli; Pasquale Miranda; Claudio Cavazzuti; Alessandra Sperduti; Marco Pacciarelli; Simon Stoddart; Paula Reimer; Caroline Malone; Luca Bondioli; Wolfgang Müller (Scientific Reports, 2023)
Abstract The Early Iron Age in Italy (end of the tenth to the eighth century BCE) was characterized by profound changes which influenced the subsequent political and cultural scenario in the peninsula. At the end of this period people from the eastern Mediterranean (e.g. Phoenicians and Greek people) settled along the Italian, Sardinian and Sicilian coasts. Among local populations, the so-called Villanovan culture group—mainly located on the Tyrrhenian side of central Italy and in the southern Po plain—stood out since the beginning for the extent of their geographical expansion across the peninsula and their leading position in the interaction with diverse groups. The community of Fermo (ninth–fifth century BCE), related to the Villanovan groups but located in the Picene area (Marche), is a model example of these population dynamics. This study integrates archaeological, osteological, carbon (δ13C), nitrogen (δ15N) (n = 25 human) and strontium (87Sr/86Sr) isotope data (n = 54 human, n = 11 baseline samples) to explore human mobility through Fermo funerary contexts. The combination of these different sources enabled us to confirm the presence of non-local individuals and gain insight into community connectivity dynamics in Early Iron Age Italian frontier sites. This research contributes to one of the leading historical questions of Italian development in the first millennium BCE.